Rapid evolution of antioxidant defence in a natural population of Daphnia magna. (4th May 2016) - Oexle, S.; Jansen, M.; Pauwels, K.; Sommaruga, R.; De Meester, L.; Stoks, R.
Abstract: Natural populations can cope with rapid changes in stressors by relying on sets of physiological defence mechanisms. Little is known onto what extent these physiological responses reflect plasticity and/or genetic adaptation, evolve in the same direction and result in an increased defence ability. Using resurrection ecology, we studied how a natural Daphnia magna population adjusted its antioxidant defence to ultraviolet radiation (UVR) during a period with increasing incident UVR reaching the water surface. We demonstrate a rapid evolution of the induction patterns of key antioxidant enzymes under UVR exposure in the laboratory. Notably, evolutionary changes strongly differed among enzymes and mainly involved the evolution of UV‐induced plasticity. Whereas D. magna evolved a strong plastic up‐regulation of glutathione peroxidase under UVR, it evolved a lower plastic up‐regulation of glutathione S‐transferase and superoxide dismutase and a plastic down‐regulation of catalase. The differentially evolved antioxidant strategies were collectively equally effective in dealing with oxidative stress because they resulted in the same high levels of oxidative damage (to lipids, proteins and DNA) and lowered fitness (intrinsic growth rate) under UVR exposure. The lack of better protection against UVR may suggest that the UVR exposure did not increase between both periods. Predator‐induced evolution to migrate to lower depths that occurred during the same period may have contributed to the evolved defence strategy. Our results highlight the need for a multiple trait approach when focusing on the evolution of defence mechanisms.